2017
DOI: 10.1111/hsc.12500
|View full text |Cite
|
Sign up to set email alerts
|

The health and well‐being of children and young people who are looked after: Findings from a face‐to‐face survey in Glasgow

Abstract: Evidence suggests children and young people who are looked after (LACYP) may have poorer health outcomes than children and young people in the general population, particularly in relation to mental health. This paper discusses findings from a survey of the health and well-being of LACYP in Glasgow. A structured questionnaire used in the 2010 Glasgow Schools Survey (GSS) was adapted and administered in face-to-face interviews with 130 young people aged 11-18 in 2014-2015 to investigate various aspects of health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In the aforementioned study by Rees (2013), the mean self-report SDQ total difficulties score (14.8) was slightly lower than the mean carer-report score (16.3), though not substantially so. In a recent survey of Glasgow children in OOHC (N ¼ 130, 78% family-based), the mean self-report SDQ total difficulties score (11.9) was comparable to the mean self-report score for adolescents in the general community (11.2), obtained in a 2010 Glasgow Schools Survey (Vincent & Jopling, 2018), which indicates that those adolescents in care reported a normative distribution of difficulties. Unless otherwise stated, refers to CBCL/YSR total problems, externalizing problems, and internalizing problems.…”
Section: Checklist Scores In Clinical Rangesmentioning
confidence: 67%
See 2 more Smart Citations
“…In the aforementioned study by Rees (2013), the mean self-report SDQ total difficulties score (14.8) was slightly lower than the mean carer-report score (16.3), though not substantially so. In a recent survey of Glasgow children in OOHC (N ¼ 130, 78% family-based), the mean self-report SDQ total difficulties score (11.9) was comparable to the mean self-report score for adolescents in the general community (11.2), obtained in a 2010 Glasgow Schools Survey (Vincent & Jopling, 2018), which indicates that those adolescents in care reported a normative distribution of difficulties. Unless otherwise stated, refers to CBCL/YSR total problems, externalizing problems, and internalizing problems.…”
Section: Checklist Scores In Clinical Rangesmentioning
confidence: 67%
“…Mean T-scores and "T score equivalents" of mean raw scores Family-based care. Seven of the reviewed studies contrasted mean carer-report and self-report mental health checklist scores for adolescents solely or predominantly residing in family-based (i.e., foster and/or kinship) care, and one study contrasted SDQ scores reported by children in OOHC and a local community sample (Vincent & Jopling, 2018). Two were the NSCAW CW and LTFC cohorts and another was the Australian foster care survey, described in the previous section.…”
Section: Checklist Scores In Clinical Rangesmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity (PA) is an important health behaviour that is associated with a multitude of physical and psychological health benefits (Ahn & Fedewa, 2011;Kirkcaldy et al, 2002;Motta, McWilliams, Schwartz, & Cavera, 2012;Pate et al, 2013) and -due to the social interaction that often occurs as part of PA participation -is associated with benefits for young people's social development (Eime et al, 2013). While there is limited evidence regarding the PA levels of young people in care, the evidence that is available demonstrates that this population do not meet PA recommendations (i.e., 60 minutes of moderate to vigorous activity on a daily basis, Dowda et al, 2009;Vincent & Jopling, 2018;World Health Organisation, 2010). Indeed, one study in the United States found that young people in foster care or residential care were less likely to achieve PA recommendations when compared to their peers in the general population, who lived at home with their parents (i.e., single parent, two parents, and step-parents) (Ornelas, Perreira, & Ayala, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…They are also at increased risk of early initiation of alcohol, tobacco, and drugs and tend to use these substances more frequently and heavily than do their peers and are more likely to develop problematic use (Braciszewski & Stout, ; Kepper, van den Eijnden, Monshouwer, & Vollebergh, ; Thompson & Auslander, ; von Borczyskowski, Vinnerljung, & Hjern, ). The findings from a recent study, however, suggest that some looked‐after young people may have rates of tobacco and alcohol use similar to those of their peers, although drug use rate was higher (Vincent & Jopling, ).…”
Section: Introductionmentioning
confidence: 99%